Two Years Clinical Registry Follow Up of Endothelial Progenitor Cell Capture Stent versus Sirolimus-Eluting Bioabsorbable Polymer-Coated Stent versus Bare Metal Stents in Patients Undergoing Primary Percutaneous Coronary Intervention for ST Elevation Myocardial Infarction - Chong, E. (2016)
American Heart Association Annual Scientific Congress